Akhlakul karimah dalam berpolitik : kumpulan pidato Muswil III PPP - Hasan Metareum, Ismail, 1929- (Jakarta : Pustaka Panjimas, 1995)
Collection of speeches of the chairman of Partai Persatuan Pembangunan, at various regional meetings; political parties in Indonesia; Islam and politics; politics and government
Keywords: Partai Persatuan Pembangunan (Indonesia); Indonesia -- Politics and government -- 1966-1998; Indonesia -- Economic conditions -- 1945-